Enhancing Residential Property Sales with Integrated Marketing Communication Strategies - Harys Kristanto; Savira Arumdini; Muhammad Fardhon (UPY Business and Management Journal (UMBJ), 2026)
Purpose: The rapid urbanization and population growth in Indonesia have significantly heightened the demand for housing, particularly in suburban regions like Bekasi Regency. As a strategic satellite city near Jakarta, Bekasi has emerged as an attractive location for residential investment due to its accessibility, infrastructural advancements, and economic development. This study investigates the impact of Integrated Marketing Communication (IMC) strategies on consumer interest in residential property purchases within Bekasi Regency. Methodology: Employing a qualitative research design, thematic analysis was conducted using NVivo software on data obtained through in-depth interviews and focus group discussions with marketing experts, developers, and prospective buyers. The research examines how IMC tools—such as advertising, public relations, and digital marketing—convey a cohesive brand message and foster consumer trust. Findings: The findings underscore the importance of consistent and targeted communication in strengthening consumer engagement and purchase intent. Originality: This study presents a relevant and timely contribution to the existing literature on real estate marketing and Integrated Marketing Communication (IMC), particularly within the Indonesian suburban context. By integrating the Theory of Planned Behavior (TPB) and the AIDA model within a qualitative framework, the research offers a nuanced perspective on how consumer behavior is influenced by cohesive marketing strategies in property purchasing decisions.